1967
DOI: 10.1111/j.1365-2621.1967.tb09701.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Fat and Protein on Lipid Composition and Oxidation in Chicken Muscle

Abstract: SUMMARY— Samples of white muscle (pectoralis major) were taken from 100 male, broiler‐type chickens which had been reared to 58 days of age on rations differing in protein level (16 or 24%) and in type of supplemental fat (5% of coconut oil, beef tallow, safflower oil or menhaden oil). Lipids were extracted from each sample and fractionated into (1) neutral lipids, (2) cephalin, and (3) lecithin. The fatty acid content of each fraction was determined by gas liquid chromatography (GLC). Lipid oxidation was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
1

Year Published

1968
1968
1990
1990

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 18 publications
3
7
1
Order By: Relevance
“…The observation (Peng and Dugan, 1965;Marion et al, 1967) that cephalin fatty acids were high in 18:0 and 20:4 while lecithin was higher in 16:0 is supported by the present study. However, the observation (Peng and Dugan, 1965) that the 18:0 of cephalin was primarily in the ethanolamine phosphatide rather than the serine phosphatide is not supported by the present study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The observation (Peng and Dugan, 1965;Marion et al, 1967) that cephalin fatty acids were high in 18:0 and 20:4 while lecithin was higher in 16:0 is supported by the present study. However, the observation (Peng and Dugan, 1965) that the 18:0 of cephalin was primarily in the ethanolamine phosphatide rather than the serine phosphatide is not supported by the present study.…”
Section: Discussionsupporting
confidence: 91%
“…161, University oi Georgia College of Agriculture Experiment Stations, Georgia Station, Experiment, Ga. 30212 b 1st Lieutenant, U. S. Army, Food Service Division, U. S. Army Quartermaster School, Fort Lee, Virginia 23801. and since it is apparent from recent studies (Acosta et al, 1966;Marion and Forsythe, 1964;Davidkova and Khan, 1967;Marion et al, 1967) that lipids of avian tissues are very unstable, further characterization appeared worthwhile. Therefore, the present study was undertaken with the objective of determining by chromatographic methods the level and fatty acid composition of lipids in tissues of chickens at two ages and of both sexes.…”
Section: Introduction T He Lipids Of Various Organs Andmentioning
confidence: 98%
See 1 more Smart Citation
“…Igene et al (1981) found during frozen storage of chicken meat the PC decreased about 26.9% and PE 43.6%. Marion et al (1967) reported the 22 carbon fatty acids with four or five double bonds in chicken muscles cephalin and lecithin positively correlated with TBA. Igene et al (1980) clearly showed during frozen stroage, the polyenoic fatty acids of PC and PE were not stable and underwent autoxidative degradation.…”
Section: Introductionmentioning
confidence: 96%
“…Entirely different types of microflora predominated in later stages of storage on poultry meat in permeable compared to impermeable films (Barnes, unpublished). Marion and Woodroof (1966) and Marion et al (1967) used the TBA test with broiler meat to determine the relationship of composition of the broiler feed to oxidative deterioration of the meat during storage at 2°C. Lea (1934) found that in birds stored at 0° to minus 1°C, greater oxidation (as measured by peroxide oxygen) of skin fat occurred in air than in C0 2 , but significant differences did not appear until after at least a month of storage.…”
mentioning
confidence: 99%